Análisis de la ordenanza que regula la tenencia de la fauna urbana en el cantón Latacunga. - Barbosa Reyes, Carlos Felipe (2021)
The present investigative work on the analysis of the Ordinance that regulates the possession of urban fauna in the Latacunga canton, has as a problem the animal abuse that afflicts society, the main objective is to analyze the ordinance that regulates the possession of urban fauna to determine its relationship with animal welfare in the Latacunga canton. This study frames the urban areas of the canton, has a qualitative and quantitative approach and a descriptive analysis; with the support of data collection instruments such as: bibliographic observation - documentary, interview and surveys that allowed the investigation of the Constitution of the Republic of Ecuador, Comprehensive Organic Penal Code (COIP), Organic Law of Animal Welfare (LOBA), Review and analysis of the Ordinance of the Municipal Decentralized Autonomous Government (GADM) of the Canton Latacunga that are the legal basis to safeguard the integrity and animal welfare. The results obtained in this research allowed to identify that there is a Municipal Ordinance that regulates the possession of urban fauna, affecting animal welfare, at the same time it is discerned that there is no knowledge of it among the guardians of companion animals and the community usually. It is recommended to carry out training, dissemination, dissemination and faithful compliance with this Ordinance.